2019
DOI: 10.26434/chemrxiv.9642071
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GPU-Accelerated Implementation of Continuous Constant pH Molecular Dynamics in Amber: pKa Predictions with Single-pH Simulations

Abstract: This paper reports a GPU-accelerated implementation and testing data of the generalized Born based continuous constant pH molecular dynamics method in the Amber package.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 50 publications
1
11
1
Order By: Relevance
“…Our analysis revealed that the coupling is communicated through the flexible intersection of TM4 and TM11, whereby changes in the protonation states of Asp133 and Asp163 affect their hydrogen-bonding patterns. Consistent with our previous findings that deprotonated aspartates tend to be stabilized by accepting hydrogen bonds (23,24), the depro- tonated Asp163 is a hydrogen bond acceptor to the sidechain hydroxyl of Thr132 and the backbone amides of Ala131 as well as Thr132 (Fig. 2C).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Our analysis revealed that the coupling is communicated through the flexible intersection of TM4 and TM11, whereby changes in the protonation states of Asp133 and Asp163 affect their hydrogen-bonding patterns. Consistent with our previous findings that deprotonated aspartates tend to be stabilized by accepting hydrogen bonds (23,24), the depro- tonated Asp163 is a hydrogen bond acceptor to the sidechain hydroxyl of Thr132 and the backbone amides of Ala131 as well as Thr132 (Fig. 2C).…”
Section: Resultssupporting
confidence: 91%
“…Coupled proton titration is a phenomenon, whereby protonation/deprotonation of two residues affects each other, resulting in irregular titration curves and the necessity to invoke a two-proton model for calculating macroscopic pKas (22). Typically, the coupled residues are hydrogen bonded to each other, such as the aspartyl dyad in enzymes (23,24), or spatially proximal to each other, such as the adjacent Asp407/Asp408 in the E. coli multidrug efflux transporter AcrB, which pumps out one drug molecule for two protons (17). Interestingly, we found that the titration curve of Asp163 in K300A NhaA is irregular (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The most recently developed CpH methods enable such calculations with either coarse-grained force fields or full-atom representations using classical or polarized force fields 7-12 . The evaluation of pKa values for all the residues of protein systems of interest remains a computational challenge, however, despite considerable improvements in speed 7, 9 . ECpH lessens this burden somewhat by requiring the knowledge of individual pKa values only for key residues.…”
Section: Discussionmentioning
confidence: 99%
“…To counter this, many groups have applied λ-dynamics, based off pioneering work by Brooks et al 20 (in turn based on earlier work with other thermodynamic properties in mind), 21,22 which treats the protonation state of individual amino acid sites as continuous degrees of freedom rather than discrete ones sampled distinctly. [23][24][25] Other efforts focus on enhancing/accelerating conformational sampling through GPU processing 26 or replica exchange. 27,28 Ultimately, regardless of solvation, one struggle for all CpHMD methods is verification of the ensemble of conformational and protonation states they generate, due to paucity of complementary experimental results.…”
Section: Introductionmentioning
confidence: 99%